Dwie sylwetki współczesnej ukraińskiej literatury popularnej - Łada Łuzina i Maryna Sokolian = Łada Łuzina and Maryna Sokolian - two figures of contemporary Ukrainian popular literature - Hajder, Tatiana (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article is devoted to one of the current issues of Ukrainian literary studies, namely popular literature and its role in shaping contemporary popular culture. On the example of the work of two well-known Ukrainian authors: Łada Łuzina and Maryna Sokolian, an attempt was made to describe and analyse the motifs most often appearing in their work. These are folklore, demonological and Christian motives.
Keywords: Sokolian, Maryna (1979 -); Łuzina, Łada (1972 -); literatura popularna; folklor; motyw; popular literature; folklore; motive